Effects of static magnetic fields on cognition, vital signs, and sensory perception: a meta-analysis - Heinrich, Angela; Szostek, Anne-Katharina; Nees, Frauke; Meyer, Patric; Semmler, Wolfhard; Flor, Herta (Journal of magnetic resonance imaging, 2011)
To evaluate whether cognitive processes, sensory perception, and vital signs might be influenced by static magnetic fields in magnetic resonance imaging (MRI), which could pose a risk for health personnel and patients, we conducted a meta-analysis of studies that examined effects of static magnetic fields. Studies covering the time from 1992 to 2007 were selected. Cohen's d effects sizes were used and combined in different categories of neuropsychology (reaction time, visual processing, eye-hand coordination, and working memory). Additionally, effects of static magnetic fields on sensory perception and vital signs were analyzed. In the category “neuropsychology,” only effects on the visual system were homogeneous, showing a statistically significant impairment as a result of exposure to static magnetic fields (d = −0.415). Vital signs were not affected and effects on sensory perceptions included an increase of dizziness and vertigo, primarily caused by movement during static magnetic field gradient exposures. The number of studies dealing with this topic is very small and the experimental set-up of some of the analyzed studies makes it difficult to accurately determine the effects of static magnetic fields by themselves, excluding nonspecific factors. The implications of these results for MRI lead to suggestions for improvement in research designs. J. Magn. Reson. Imaging 2011;. © 2011 Wiley-Liss, Inc.
First published: 12 July 2011
Gesehen am 04.10.2022